Edukasi Pendaftaran Online Pasien di Unit Rawat Jalan RSUD Dr. R. Soedarsono Kota Pasuruan - Fairuza, Najwa; Sulistyawati, Ety Diana; Sari, Ika Puspita; Yusmanisari, Eka (Jurnal Abdimas Jatibara, 2023)
RSUD Dr. R. Soedarsono, Pasuruan City, people are still experiencing difficulties registering online. The community has to come directly to the hospital and have to queue which turns out to take a lot of time. Registration can also be done via Handpone. From this background, we are interested in carrying out outpatient online registration education using the E New Purut Application. Where this application is expected to help the community in registering for treatment which can be done using a mobile phone and can be done online via the internet. Before carrying out the activity, the location must be guarded first. In guarding this location, discussions are held regarding the time for carrying out activities by taking into account input from the Hospital. The activities carried out are in the form of Online Registration Education at the Outpatient Unit at RSUD Rr. R.SoedarsonoThis community activity aims to educate the public about online registration, to make it easier for the public to register, and to make it easier for patients not to have to queue long at the counter when seeking treatment at the hospital